(untitled) (Revista Archai, 2019)
The aim of the paper will be to analyze the different strategies that the Stoics of the Imperial times designed in order to put our sense of justice on hold, due to the fact that it is deemed responsible for certain attitudes which do not contribute to our search for eudaimonía. I will organize such strategies in two groups: the first one corresponds to the strategies that target the idea that an injustice has been committed; the second one corresponds to the ones that aim to show that there are more convenient attitudes towards injustice than the demand for punishment or the desire for revenge. I will end by pointing at the difficulty of reconciling both sets of strategies, and I will suggest a possible way to account for that difficulty.